Effects of the Perceived Self-efficacy Promoting Program on Knowledge and Skills in Emergency Medical Services among Emergency Medical Responders at Sam Ngam District, Phichit Province - Samingnil, Athittanan; Jariya, Wutthichai (Journal of The Royal Thai Army Nurses, 2023)
This quasi-experimental research purposed to investigate the effects of the perceived self-efficacy promoting program on knowledge and skills in emergency medical services among emergency medical responders at Sam Ngam District, Phichit Province. Such a program was designed regarding Bandura’s self-efficacy theory. The sample was 60 emergency medical responders divided into two groups, 30 in experimental group and 30 in control group. The experimental group received the self-efficacy promoting program on emergency medical services among emergency medical responders. Questionnaires assessing knowledge and skills in emergency medical services were used to collect data. The reliability (KR20) of the questionnaires was examined, and the results were 0.82 and 0.71, respectively. Data were analyzed by using percentage, mean and standard deviation. The two-way repeated measure ANOVA was utilized to compare the mean score of knowledge and skills in emergency medical services between the experimental group and the control group, while the one-way repeated measure ANOVA was used to compare such mean scores within experimental group. The results revealed that: 1) at the post-test stage and 2-month follow-up period, the experimental group had a higher mean score of knowledge and skills in emergency medical services than before the experiment at a significant level.05 (F= 32.839, p-value<.05 และ F = 79.530, p-value<.05, respectively); 2) at the post-test stage and 2-month follow-up period, the experimental group had higher mean score of knowledge and skills in emergency medical services than the control group at a significant level.05 (F = 40.390, p-value<.05 and F = 36.295, p-value<.05, respectively)